Developing an equipotential line method for the optimal design of an energy station location in a district heating system. (15th April 2020) - Wu, Di; Liu, Zhijian; Han, Zhonghe; Ma, Fanfan; Yang, Xinyan; Zhang, Han; Jin, Guangya
Highlights: Equipotential line method of relative cost was proposed. The optimal energy station location with relative cost, about 89.22%, is determined intuitively. Triple-generation system was combined with distributed variable-frequency speed pump heating system. Economic analyses were carried out for the coupling system in terms of payback period. Reliability of two strategies was compared for the coupling system. Abstract: The district heating system with distributed variable-frequency speed pumps (DVFSP) can provide substantial energy savings. Moreover, the energy station location has a great impact on the capital expenditure of heating system. Therefore, to determine the optimal energy station location in DVFSP system, this paper initially built a theoretical model of a DVFSP district heating system based on a cost-oriented index. Subsequently, an equipotential line method was illustrated and applied to a case study. This novel method can intuitively present the district distribution of the relative cost ( RC network ) of DVFSP district heating system, which can conveniently determine the optimal location of an energy station. In the case study, six oval equipotential RC network lines were described. The maximum RC network reached 137.04% in the E4 location, and the minimum RC network was 89.22% in the E11 location. The results showed that the optimal energy station location was near the district load center and biased to the side with higher building loads. Finally, a new energy utilization mode that coupled a combined cooling, heating and power (CCHP) system and a DVFSP district heating system was proposed. Economic analyses were carried out for the coupled system based on the following electric load (FEL) strategy and the following thermal load (FTL) strategy. The results confirmed that, in terms of the payback period and partial load rate ( PLR ) of the prime mover, the FEL strategy was more suitable for the coupled system. These results can provide guidance for district heating system design and management.